2020
DOI: 10.1101/2020.01.19.911305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anisotropic mineralized collagen scaffolds accelerate osteogenic response in a glycosaminoglycan-dependent fashion

Abstract: Regeneration of critically-sized craniofacial bone defects requires a template to promote cell activity and bone remodeling. However, induced regeneration becomes more challenging with increasing defect size. Methods of repair using allografts and autografts have inconsistent results, attributed to age-related regenerative capabilities of bone. We are developing a mineralized collagen scaffold to promote craniomaxillofacial bone regeneration as an alternative to repair. Here, we hypothesize modifying the pore … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…However, the large scale of the defects tested likely require efforts to boost cell recruitment and activity. Key modification include: the use of intraoperative adipose-derived stem cells seeding to boost healing [58]; modifications to the glycosaminoglycan content and pore size or orientation of the mineralized collagen scaffold to promote greater cell migration into the defect [57,59] and the potential to incorporate biomolecular signals (e.g., transiently incorporated BMP2, VEGF) or modify the mineral composition (e.g., inclusion of zinc ions) to promote proliferation, osteogenesis, or angiogenic activity [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…However, the large scale of the defects tested likely require efforts to boost cell recruitment and activity. Key modification include: the use of intraoperative adipose-derived stem cells seeding to boost healing [58]; modifications to the glycosaminoglycan content and pore size or orientation of the mineralized collagen scaffold to promote greater cell migration into the defect [57,59] and the potential to incorporate biomolecular signals (e.g., transiently incorporated BMP2, VEGF) or modify the mineral composition (e.g., inclusion of zinc ions) to promote proliferation, osteogenesis, or angiogenic activity [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…The regeneration of complex CMF bone defects requires the interaction of biomaterial implants with multiple cell types. Previously, mineralized collagen scaffolds fabricated with CS6 glycosaminoglycan content have been shown to promote greater calcium and phosphorous mineral after 28 days of hMSC culture compared to CS4- and Heparin-containing scaffolds [65]. In order to successfully regenerate CMF defects, we must consider not only osteogenesis, but also mature vessel formation, resorption of the implant by osteoclasts, and the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…136,137 Additionally, glycosaminoglycans are important constituents of healthy bone and specically glycosaminoglycans chondroitin-6-sulfate and heparin sulfate have been shown to promote mineral formation in mineralized collagen scaffolds. 138 Glycosaminoglycans have dramatic effects on other cells and processes such as angiogenesis and inammation. Studies using chondroitin sulfate have demonstrated an inhibitory effect of this glycosaminoglycan on monocyte migration in vitro and thus a potential anti-angiogenic effect in vivo.…”
Section: Balancing Multiple Cell Types and Interactionsmentioning
confidence: 99%
“…147 This has also held true for anisotropic pores in mineralized collagen scaffolds, where alignment caused an increase in osteogenic gene expression and mineralization. 138 This alignment may also have benecial effects in directing vessel network formation through channel-like materials and providing guidance for angiogenesis. 148 Pore size and shape can effect multiple cell types, and thus there is some speculation on the best pore size for enhancing osteogenesis due to multiple cell interactions.…”
Section: Balancing Multiple Cell Types and Interactionsmentioning
confidence: 99%